Sociocultural factors, academic performance, and intercultural university education in the Peruvian Amazon - Morales Rocha, José Luis; Coyla Zela, Mario Aurelio; Serruto Medina, Genciana; Vargas Torres, Nakaday Irazema; Asencios Tarazona, Vitelio; Arroyo Japura, Gregorio; Huanca Frias, José Oscar (Frontiers in Education, 2024)
The educational context in the Peruvian Amazon is moderately complex because of the interaction between students from 23 indigenous peoples, with a preponderance of Shipibo-Conibo, Ashaninka, Awajun, Shawi, Yanesha, Wampis, Quechua, and Cacataibo, among the most representative and in that order, with culturally different knowledge and worldviews. Thus, the university becomes a center of tolerance, recognizing and accepting the identity of others and coexisting with mestizo students from urban areas. This study aimed to determine the sociocultural and educational factors influencing academic performance in a virtual teaching context for intercultural university education in the Peruvian Amazon. A neural network model was applied to a sample of 162 students from a population of 1,835 students at an intercultural university in the Peruvian Amazon. Furthermore, 54% of the students are of mestizo origin, and 46% belong to the indigenous population. It was concluded that economic dependence on the family, failing midterm exams, feeling isolated and alone, and conflicts with a family member influence academic performance.